The actual financial crisis and the lessons that can be learned - MAURI, Arnaldo; BAICU, Claudia (Annals of Spiru Haret University. Economic Series, 2009)
Since the development of modern banking in Italian renaissance, financial crises have from time to time affected institutions and markets and have raised concern about stability of financial systems. Authorities and scholars around the world are investigating the matter discussing on the proximate and more distant causes of crises and gaining lessons from the experience of the past, on the steps that could be taken to minimize vulnerability of financial systems. The paper focuses on the analysis of the most important factors contributing to the triggering of the current financial crisis, the peculiarities and the lessons of the crisis.